Fish as food: projections to 2020 under different scenarios - Delgado, Christopher L.; Rosegrant, Mark W.; Wada, Nikolas; Meijer, Siet; Ahmed, Mahfuzuddin (International Food Policy Research Institute, 2002)
This paper reports results of incorporating fish into IMPACT, a global model of food supply and demand that estimates market-clearing prices to 2020 for 32 commodities in 36 regions. It summarizes results for production, consumption, net exports and real price changes for 10 economic categories of fisheries items, disaggregated into 15 geographic regions of the world. Under the medium-variant scenario for the uncertain capture fisheries sectors, global production of food fish is projected to rise by 1.5% annually through 2020, with two-thirds of this from aquaculture, whose share in total food fish production rises to 41%. Global per capita fish consumption is projected to be 17.1 kg in 2020, with sensitivity analysis indicating a margin of 2 kg/capita either way based on extreme scenarios for capture and aquaculture. Most growth will occur in developing countries, which will account for 79% of food fish production in 2020. China's share of world production will continue to expand, while that of Japan, the EU, and former USSR will continue to contract. Real fish prices will rise 4 to 16% by 2020, while meat prices will fall 3%. Fishmeal and oil prices will rise 18%; use of these commodities will increasingly be concentrated in carnivorous aquaculture. Growing domestic demand will dampen fish exports from developing countries. Sensitivity analysis incorporating a very pessimistic view of capture fisheries leads to escalating food fish prices (+69% for high-value finfish) and soaring fishmeal prices (+134%), whereas an optimistic view of increased investment in aquaculture lowers real prices of low value food fish (-12%), and raises fishmeal prices (+42%). -- Authors' Abstract